Data Synchronization in Digital Twin for a Lab-Scale Drone Factory - Vishwanath Nagarajan, Aniruth; Janaswami, Gnyaneshwar (My University, 2024)
Industry 4.0 has introduced new technologies aimed at revolutionizing and digitizing the manufacturing sector. Among these, Digital Twin stands out as a leading technology for industrial digitalization. This thesis examines the integration of Digital Twin with an actual production system to achieve data synchronization. A lab-scale drone factory serves as the test bed for this research. Through an extensive literature review, the study identifies essential communication technologies and architectures that facilitate the connection between Digital Twin and real systems. The project’s methodologies involve developing a Digital Model, selecting a communication protocol, establishing a connection between the Digital Model and the real system, importing and exporting data between the Digital Twin and a server, and verifying the control of the real system via the Digital Twin and vice versa. The findings demonstrate that the Digital Twin can replicate and control the real system, offering suggestions for production parameter improvements. The study concludes by discussing the implications of future research on this thesis and detailing the steps and advantages of integrating event log data into PlantSim
Keywords: Digital Twin; Industry 4.0; Real Time Data Synchronization; OPC UA; Internet of Things